PENGENALAN METODE JARIMATIKA DALAM PEMBELAJARAN BERHITUNG PERMULAAN DI TK NEGERI PEMBINA - Widya, Ratna; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the introduction of the Jarimatic method in early numeracy learning for the children aged of 5-6 years old at TK Negeri Pembina Pontianak Barat. The research methodÂ was the descriptive qualitative approach. The subjects in this study were the teachers and children in group B1. The data collection techniques that were used: direct communication, direct observation and documentary studies. In analyzing the data that was done by finding and compiling the obtained data then describing it, selecting the important ones, making conclusions so that the obtained data can be developed and evaluated. It can be concluded that the introduction of Jarimatika method in early numeracy learning for children aged 5-6 years old in TK Negeri Pembina was given repeatedly by the teacher through three stages, namely the active stage, the iconic stage, and the symbolic stage. The early numeracy ability from the children aged 5-6 years old at the enactive, iconic, and symbolic stages of theJarimatic method Introduction was gradually developed. It will be better if the games and media used by the teacher in introducing the Jarimatic method is made to be more appealing so that it will be very interesting to learn about calculation.Â Keywords: Jarimatic Method, Early Numeracy Learning, Children 5-6 Years Old